Low status, humiliation, dopamine and risk of schizophrenia - Selten, Jean Paul; Ormel, Johan (Psychological medicine, 2023)
The social defeat hypothesis of schizophrenia, which proposes that the chronic experience of outsider status or subordinate position leads to increased striatal dopamine activity and thereby to increased risk, has been criticized. The aims of this paper are to improve the definition of defeat and to integrate the social defeat hypothesis with the neurodevelopmental hypothesis. Marmot advanced the idea that low status is pathogenic in that it is associated with a lack of social participation and a lack of autonomy. Given the similarity with outsider status and subordinate position, we re-define social defeat as low status. From this new perspective it is also likely that pre-schizophrenic impairments (of neurodevelopmental origin or not) are pathogenic in that they contribute to low status. The effect of low status may be enhanced by repeated exposure to humiliation, but few studies have measured this variable. Since most individuals exposed to low status do not develop schizophrenia, we propose that this risk factor increases the risk of disorder in the presence of a poor homeostatic control of dopamine neurons in midbrain and dorsal striatum. This is consistent with studies of healthy subjects which report a negative association between low socio-economic status and dopamine D2/D3 receptor availability in the dorsal striatum. In this new version of the social defeat hypothesis we propose that the combination of low status, repeated humiliation and poor homeostatic control of dopamine neurons in midbrain and dorsal striatum leads to increased striatal dopamine activity and thereby to an increased risk of schizophrenia.